TERRORISM AND GUERRILLA WARFARE AS TWO FORMS OF INSURGENCY - Gailiūnas, Egidijus (Politologija, 2015)
This article deals with the phenomenon of political violence. The concept of “armed resistance” (Lithuanian: ginkluotas pasipriešinimas) is introduced to describe political violence perpetrated by non-state actors or subnational groups. The Lithuanian concept of “armed resistance” in general corresponds to the English concept of “insurgency”. Many problems related to the definitions of concepts of “insurgency”, “guerrilla warfare” and “terrorism” are pointed out. The article states that the identified concepts are often used incorrectly in foreign and Lithuanian academic publications. Very often these concepts of “insurgent”, “guerrilla fighter”, and “terrorist” are used as synonyms. One of the main reasons for misuse of the mentioned concepts is the lack of related academic literature. Misuse of the terms insurgents, guerrillas and terrorists by official governmental institutions is also underlined. It is argued in the article that proper understanding of the armed resistance is needed. To get such an understanding one needs to distinguish political violence and non-political or apolitical violence. Violence used by armed resistance groups (guerrilla and terrorist groups) is inevitably political in its aims and motives. That is why it is called political violence. Criminals and pathological murders also use violence but their aims and motives are different. Criminal groups use violence to obtain money or to acquire material goods. Pathological murders see violence as an end in itself. Usually they are not interested in politics, profit or material goods. The main idea of this article is that, because of the numerous recent researches made in the field of political violence (insurgency, terrorism, and guerrilla warfare), different strategies of armed resistance may be more or less clearly defined. Guerrilla warfare and terrorism are different strategies or different strategic approaches used by various non-state actors. The author argues that guerrillas and terrorists should be distinguished according to four criteria: 1) targets; 2) identification signs; 3) control of territory; 4) size of operational units. Terrorists’ targets are mostly civilian ones. Guerrillas’ targets are mostly military. Terrorists do not use uniforms or other signs to identify them as combatants. Guerrillas usually have some sort of identification signs. Terrorists are not interested in control of the territory. Guerrillas want to seize or hold on territory. Terrorists usually operate in units ranging from lone assassin to five-member teams. Guerrillas mostly wage their war in platoon or company size units. The distinction between terrorism and guerrilla warfare is of crucial importance because it helps to better understand the nature of armed resistance. It should be pointed out that on the understanding and clear definitions of terrorism and guerrilla warfare depends the quality of an academic research. In addition, the distinction of guerrilla warfare and terrorism is important for the success of counter-insurgency and counter-terrorism campaigns.